Psychological health of teachers of the New Ukrainian School as the basis of their psychological readiness for creative professional activity - Pavlyk , Natalia Vasylivna; Radzimovska , Oksana Vitaliivna (Insight: the psychological dimensions of society, 2023)
The article empirically determines the interrelation of such psychological phenomena as psychological health and psychological readiness for pedagogical creativity. The purpose of the article is to establish the patterns of influence of the psychological health of teachers of the New Ukrainian School (NUS) on their psychological readiness for creative professional activity. Methods. To conduct an empirical research, the author’s psychodiagnostic methods “Teacher psychological readiness”, “Psychological health of an individual”, analysis of the percentage distribution and average values of indicators, correlation and factor analysis were used. The article presents an empirical model (structure, criteria, indicators, and methodological tools) for studying teachers’ psychological health features and psychological readiness for professional creativity. The basis of psychological readiness for pedagogical creativity amidst the NUS is the unity of pedagogical motivation, professional knowledge, skills, and creative abilities in combination with the mastery by the teacher of the functions of an educator, tutor, facilitator, and moderator. The criteria of psychological health are a healthy lifestyle, stress resistance, self-control, emotional stability, flexible thinking, social adaptation, activity, good mood, and creative realization. Results. The author presents findings of the empirical study of teachers’ features of psychological health state and the development level of their psychological readiness for creative professional activity; the interpretation of statistical data processing is given. Conclusions. A teacher’s psychological health determines the development of their psychological readiness for creative pedagogical activity: the higher the psychological health of teachers is, the higher their propensity to conduct professional creativity is. The major role in the development of psychological readiness for pedagogical creativity is played by flexible thinking, creative self-realization, emotional and volitional qualities (self-control, stress resistance) and a positive emotional state (good mood, optimism) of a teacher.
Keywords: psychological readiness, pedagogical creativity, psychological health, creative self-realization, psychological patterns